2016
DOI: 10.1155/2016/3568076
|View full text |Cite
|
Sign up to set email alerts
|

Successful Nonoperative Management of High-Grade Blunt Renal Injuries

Abstract: Current management of high-grade blunt renal trauma favors a nonoperative approach when possible. We performed a retrospective study of high grade blunt renal injuries at our level I trauma center to determine the indications and success of nonoperative management (NOM). 47 patients with blunt grade IV or V injuries were identified between October 2004 and December 2013. Immediate operative patients (IO) were compared to nonoperatively managed (NOM). Of the 47 patients, 3 (6.4%) were IO and 44 (95.6%) NOM. IO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…In 5 studies ( 9 , 15 , 18 , 20 , 22 ), rates of urinary extravasation were only available for patients with grade IV injuries and in 6 studies ( 6 , 10 , 12 , 13 , 19 , 26 ) this rate was only available for grade IV–V injuries combined. The other studies included sufficient detail to calculate rates for different combinations of renal injury grades ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 5 studies ( 9 , 15 , 18 , 20 , 22 ), rates of urinary extravasation were only available for patients with grade IV injuries and in 6 studies ( 6 , 10 , 12 , 13 , 19 , 26 ) this rate was only available for grade IV–V injuries combined. The other studies included sufficient detail to calculate rates for different combinations of renal injury grades ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…13 The paradigm shift in management based on clinical status rather than severity of the injury may be attributed to improved radiographic techniques resulting in improved grading of the injury, advancements in resuscitation techniques, and availability of interventional radiology. 14,15 Advancements in angioembolization have likely aided in shifting practice patterns. Brewer et al reported success of angioembolization in patients with grade 5 renal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high-grade renal traumas can be managed conservatively [15]. Non-operative management of high-grade traumas results in a higher kidney salvage rate (87% vs 93%) with minimal complications as a consequence of non-operative management [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that high-grade renal traumas can be managed conservatively [15]. Non-operative management of high-grade traumas results in a higher kidney salvage rate (87% vs 93%) with minimal complications as a consequence of non-operative management [15]. The success of non-operative management with high-grade renal injury has also been demonstrated in the series presented by Buckley and McAninch in which 58% of isolated grade 4 renal injuries were managed conservatively with a renal salvage rate of 88%, with no non-operative case requiring delayed nephrectomy [16].…”
Section: Discussionmentioning
confidence: 99%